Pengaruh Gaya Kepemimpinan dan Motivasi terhadap Disiplin Kerja Pegawai pada Kantor Kecamatan Babelan - Visi Khumairah Madani; Agus Dharmanto; Nita Komala Dewi (International Forum of Researchers and Lecturers, 2024)
This study was conducted to determine the effect of leadership style and motivation on employee discipline at the Babelan District office. The type of research used in this research is quantitative research. The sampling technique used a non-probability sampling technique with a saturated sample method through a questionnaire made through a questionnaire/questionnaire with the criteria of all employees of the Babelan District office totaling 52 employees. The data analysis method uses multiple linear regression. The results of this study indicate that Leadership style affects employee work discipline at the Babelan sub-district office, motivation affects employee work discipline at the Babelan sub-district office and Leadership style and motivation simultaneously or jointly affect employee work discipline at the Babelan sub-district office